Pemanfaatan Kitosan untuk Mengendalikan Antraknosa pada Pepaya (Colletotrichum gloeosporioides) dan Meningkatkan Daya Simpan Buah - Rita Yunita; Nurul Nisa Amin; Tri Asmira Damayanti (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2012)
Anthracnose (Colletotrichum gloeosporioides) is an important disease infecting fleshy fruits. The efficacy of chitosan to suppress C. gloeosporioides infection and its ability to increase the length of fruit storage was evaluated. C. gloeosporioides was isolated and purified from mature papaya. Chitosan was mixed in the potato dextrose agar, and sprayed on the surface of papaya fruit with the concentration of 0.05, 0.1, 0.25, 0.5, 0.75 and 1%. It showed that chitosan concentration of 0.75-1% inhibited C. gloeosporioides growth in vitro up to 72.17-85.21%. Application of chitosan on fruit at concentration of 0.25% suppressed the disease incidence and severity; whereas chitosan concentration of 0.75% was able to suppress the disease incidence, severity, and increase the length of fruit storage twice longer than control.Key words: anthracnose, chitosan, Colletotrichum gloeosporioides, papaya, the length of storage.